A bloom of the green worm Phyllodoce tuberculosa Kudenov, 1975 in a beach of the Southern Gulf of California, Mexico (Annelida, Errantia, Phyllodocidae). Issue 19 (18th May 2020) - Tovar-Hernández, María Ana; Ortíz-Arellano, Mónica Anabel
ABSTRACT: The massive presence of the green worm Phyllodoce tuberculosa Kudenov, 1975 on a beach of the southern Gulf of California (Mexico) is reported. It was found reaching densities of 48 ind/m 2 during low tides, 4 days before the full moon and during the full moon of March 2020. The population comprised mainly gravid females, in a sex ratio of 1:100 (1 male per 100 females). Mature oocytes measure 110–120 μm in diameter. Mature spermatozoa have a nearly spherical head, with an elliptical nucleus, a cap-like acrosome and a long flagellum (ect-aquasperm type). This is the first finding of P. tuberculosa since its description in 1975.